A storm of songs : India and the idea of the bhakti movement - Hawley, John Stratton, 1941- (Harvard University Press, 2015)
India celebrates itself as a nation of unity in diversity, but where does that sense of unity come from? One important source is a widely-accepted narrative called the "bhakti movement." Bhakti is the religion of the heart, of song, of common participation, of inner peace, of anguished protest. The idea known as the bhakti movement asserts that between 600 and 1600 CE, poet-saints sang bhakti from India's southernmost tip to its northern Himalayan heights, laying the religious bedrock upon which the modern state of India would be built. Challenging this canonical narrative, John Stratton Hawley clarifies the historical and political contingencies that gave birth to the concept of the bhakti movement. Starting with the Mughals and their Kachvaha allies, North Indian groups looked to the Hindu South as a resource that would give religious and linguistic depth to their own collective history. Only in the early twentieth century did the idea of a bhakti "movement" crystallize--in the intellectual circle surrounding Rabindranath Tagore in Bengal. Interactions between Hindus and Muslims, between the sexes, between proud regional cultures, and between upper castes and Dalits are crucially embedded in the narrative, making it a powerful political resource. A Storm of Songs ponders the destiny of the idea of the bhakti movement in a globalizing India. If bhakti is the beating heart of India, this is the story of how it was implanted there--and whether it can survive. (Publisher).